PENGARUH KOMPENSASI, LINGKUNGAN KERJA, KESELAMATAN DAN KESEHATAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN (Survei pada Karyawan Kantor Terminal Bahan Bakar Minyak PT. Pertamina (Persero) Boyolali) - Shofia Nur Sa’adah; Marjam Desma Rahadhini; Suprayitno Suprayitno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This study aims to analyze compensation, work environment, occupational safety and health (K3) on job satisfaction of employees of the Office of the Fuel Oil Terminal (TBBM) of PT. Pertamina (Persero) Boyolali. This research uses primary and secondary data. This type of research is a total sampling (census) of all TBBM employees of PT. Pertamina Boyolali. The study population was all TBBM employees of PT. Pertamina Boyolali as many as 112 employees. Data were analyzed using instrument test, classical assumption test, multiple linear regression, t test, F test, coefficient of determination. The results of the analysis show rewards for employee job satisfaction. Work environment for employee job satisfaction. Occupational safety and health (K3) affect employee job satisfaction.